Multifunctional Immunoadjuvants for Use in Minimalist Nucleic Acid Vaccines - Saed Abbasi; Satoshi Uchida (MDPI AG, 2021)
Subunit vaccines based on antigen-encoding nucleic acids have shown great promise for antigen-specific immunization against cancer and infectious diseases. Vaccines require immunostimulatory adjuvants to activate the innate immune system and trigger specific adaptive immune responses. However, the incorporation of immunoadjuvants into nonviral nucleic acid delivery systems often results in fairly complex structures that are difficult to mass-produce and characterize. In recent years, minimalist approaches have emerged to reduce the number of components used in vaccines. In these approaches, delivery materials, such as lipids and polymers, and/or pDNA/mRNA are designed to simultaneously possess several functionalities of immunostimulatory adjuvants. Such multifunctional immunoadjuvants encode antigens, encapsulate nucleic acids, and control their pharmacokinetic or cellular fate. Herein, we review a diverse class of multifunctional immunoadjuvants in nucleic acid subunit vaccines and provide a detailed description of their mechanisms of adjuvanticity and induction of specific immune responses.